Detection and epidemic dynamic of ToCV and CCYV with Bemisia tabaci and weed in Hainan of China - Xin Tang; Xiaobin Shi; Deyong Zhang; Fan Li; Fei Yan; Youjun Zhang; Yong Liu; Xuguo Zhou (Virology Journal, 2017)
Abstract Background In recent years, two of the crinivirus, Tomato chlorosis virus (ToCV) and Cucurbit chlorotic yellows virus (CCYV) have gained increasing attention due to their rapid spread and devastating impacts on vegetable production worldwide. Both of these viruses are transmitted by the sweet potato whitefly, Bemisia tabaci (Gennadius), in a semi-persistent manner. Up to now, there is still lack of report in Hainan, the south of China. Methods We used observational and experimental methods to explore the prevalence and incidence dynamic of CCYV and ToCV transmitted by whiteflies in Hainan of China. Results In 2016, the chlorosis symptom was observed in the tomato and cucumber plants with a large number of B. tabaci on the infected leaves in Hainan, China, with the incidence rate of 69.8% and 62.6% on tomato and cucumber, respectively. Based on molecular identification, Q biotype was determined with a viruliferous rate of 65.0% and 55.0% on the tomato and cucumber plants, respectively. The weed, Alternanthera philoxeroides near the tomato and cucumber was co-infected by the two viruses. Furthermore, incidence dynamic of ToCV and CCYV showed a close relationship with the weed, Alternanthera philoxeroides, which is widely distributed in Hainan. Conclusion Our results firstly reveal that the weed, A. philoxeroides is infected by both ToCV and CCYV. Besides, whiteflies showed a high viruliferous rate of ToCV and CCYV. Hainan is an extremely important vegetable production and seed breeding center in China. If the whitefly can carry these two viruses concurrently, co-infection in their mutual host plants can lead to devastating losses in the near future.